2020
DOI: 10.21475/ajcs.20.14.03.p2325
|View full text |Cite
|
Sign up to set email alerts
|

Composition and antimicrobial activity of essential oil of yarrow (Achillea millefolium L.)

Abstract: The medicinal plant yarrow (Achillea millefolium L.) belongs to the Asteracea family. It is being used in the pharmacological, food, and cosmetic industry. The economic importance of yarrow resides in its essential oil (EO). This plant is used in traditional medicine as the EO has properties which range from antibacterial, antifungal, anti-inflammatory, anti-oxidant and antitumor activities. The objective of this study was to identify chemical components and EO content of yarrow, as well as its antimicrobial a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…According to the previous research by Beigi et al [ 41 , 67 , 75 ], peppermint, yarrow and chamomile are herbs with high contents of terpenes, terpenoids and phenolic compounds, which was confirmed by the peak registered at the 270 nm and as a band for 290–320 nm [ 90 , 91 , 92 ]. The chlorophyll content characteristic for plants was noticed as an extensive peak in the range of 360 to 450 nm and at 680 nm [ 93 ].…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…According to the previous research by Beigi et al [ 41 , 67 , 75 ], peppermint, yarrow and chamomile are herbs with high contents of terpenes, terpenoids and phenolic compounds, which was confirmed by the peak registered at the 270 nm and as a band for 290–320 nm [ 90 , 91 , 92 ]. The chlorophyll content characteristic for plants was noticed as an extensive peak in the range of 360 to 450 nm and at 680 nm [ 93 ].…”
Section: Resultsmentioning
confidence: 94%
“…This was confirmed by the obtained results as the contact angle of studied plants was below 90°. Again, these low values of contact angle were caused by the presence of terpenes and terpenoids in the herb composition such as menthol in Mentha piperita L. [ 36 ], bisabolol in Matricaria chamomilla L. [ 69 ] and cadinol or terpinen-4-ol in Achillea millefolium L. [ 75 ]. The lowest CA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar high activity was reported for the EO from France, where camphor and germacrene-D were reported as the main compounds. [18] On the other hand, recent research by Daniel et al [30] reported the results with much lower activities of EO from the same plant species. This EO originated from plant material collected in Brazil and had α-farnesene (31.7 %) followed by chamazulene (17.2 %), β-caryophyllene (10.3 %) and sabinene (8.8 %).…”
Section: Antimicrobial Activitymentioning
confidence: 92%
“…For this plant species, our results have shown inhibitory action in the range from 0.31 to 20 mg/mL, with S. enteritidis as the most sensitive strain, while ATCC strain of P. aeruginosa showed the highest resistance to the action of this EO. In the previous studies, which determined the MICs of the EO of A. millefolium, inhibition was exhibited against various microbial strains and was in a very wide range of concentrations such as 4.5 -72 mg/mL, [28] 0.32 -10 μl/mL, [29] 3.7 -150 mg/mL, [30] 0.1 -2 mg/mL, [18] 1-5 μg/mL, [9] and some of them even showed lack of activity at very high concentrations. In comparison to the other results, Kazemi [9] reported very significant activity of A. millefolium EO collected in Iran, which was unusually highly active as observed activity was higher than that of the tested antibiotics ampicillin and fluconazole.…”
Section: Antimicrobial Activitymentioning
confidence: 99%